Integrating VAT into EUROMOD: Documentation and results for Belgium - André Decoster; Richard Ochmann; Kevin Spiritus (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper documents the integration of microsimulation tools for direct taxation, indirect taxation, and social benefits in the context of the European tax and benefit simulator, EUROMOD. Integration has been developed in parallel for two countries: Belgium and Germany. The paper at hand documents the process and presents simulation results for the case of Belgium. An integrated database underlying EUROMOD that contains householdlevel information on income and consumption is generated. Consumption micro data from the 2009 cross section of the household budget survey for Belgium is used to impute information on spending for durable and non-durable commodities into EU-SILC data, applying regression-based imputation techniques. Engel curves are estimated at the household level for total non-durable spending, expenditures on durable goods, as well as non-durable expenditure share equations. The imputed household spending is then used to simulate the baseline VAT system in EUROMOD, for which we report an incidence analysis. Finally, several arbitrary policy reforms implementing VAT rate uniformity are analyzed with respect to their distributional impact.
Keywords: D12; D31; H24; H31; 330; budget survey; expenditure estimation; Engel curves; EUROMOD